A resonator-based dual-frequency driven atmospheric pressure plasma jet. (1st June 2022) - Bansemer, Robert; Weltmann, Klaus-Dieter
Abstract: An atmospheric-pressure argon plasma jet featuring a novel integrated resonator-based multi-frequency impedance matching is presented and briefly characterized. Two narrow RF frequency bands can be chosen for operation or used simultaneously. This includes a mode with the higher frequency value being exactly five times the lower one. Phase-resolved optical emission spectroscopy measurements show a distinct influence of the input frequency combination on the discharge dynamics. Measurements of the dissipated electrical power and the emission spectrum for each operating mode complete the basic characterization of the device. Although it is constructively much simpler and more compact than dual-frequency discharges using a conventional impedance matching system, the presented device shows an excellent performance in dual-frequency operation.